Generation of an inducible mouse model to reversibly silence Stat3. Issue 4 (23rd February 2017) - Alorro, Mariah G.; Pierce, Thomas P.; Eissmann, Moritz F.; Dijkstra, Christine; Dickins, Ross A.; Ernst, Matthias; Buchert, Michael; Masson, Frederic
Abstract: Signal transducer and activator of transcription 3 (Stat3) is a transcription factor that has many essential roles during inflammation, development and cancer. Stat3 is therefore an attractive therapeutic target in many diseases. While current Stat3 knockout mouse models led to a better understanding of the role of Stat3, the irreversible nature of Stat3 ablation does not model the effects of transient Stat3 therapeutic inhibition, and does not inform on potential dosage effects of Stat3. Using RNAi technology, we have generated a new mouse model allowing the inducible and reversible silencing of Stat3 in vivo, which mirrors the effects of specific Stat3 therapeutic interference. We showed that upon Doxycycline‐mediated activation of the Stat3 short‐hairpin RNA, Stat3 expression was efficiently reduced by about 80% in multiple organs and cell types. Moreover, Stat3 reduction was sufficient to reduce tumor burden in a clinically‐validated mouse model of gastric cancer. Finally, we demonstrated that Stat3 silencing during embryonic development led to reduced birth rate without leading to complete embryonic lethality, in contrast to full Stat3 ablation. In conclusion, this new mouse model will be invaluable to understand the effects of Stat3 therapeutic interference and Stat3 dosage effects.